2019
DOI: 10.1007/s00213-019-05408-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment decreases chronic psychosocial stress-impaired extinction and reinstatement of ethanol conditioned place preference in C57BL/6 male mice

Abstract: Rationale During the last few decades, alcohol use disorders (AUD) have reached an epidemic prevalence, yet social influences on alcoholism have not been fully addressed. Several factors can modulate alcohol intake. On one hand, stress can reinforce ethanol-induced behaviors and be an important component in AUD and alcoholism. On the other hand, environmental enrich-ment (EE) has a neuroprotective role and prevents the development of excessive ethanol intake in rodents. However, studies showing the role of EE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 91 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…They suggested that like anxiety, anger can be triggered by some stimuli in the environment, and cue exposure therapy can teach patients with anger-related disorders to reduce their anger behaviours in relation to these triggers. Cue exposure therapy is an established treatment for anxiety disorders (Bahi & Dreyer, 2020 ; Javanbakht, 2018 ; Loucks et al, 2019 ; Nonkes et al, 2012 ; Stenmark et al, 2013 ). Other studies have also shown that cue exposure therapy can effectively decrease anger feelings (Stapleton et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that like anxiety, anger can be triggered by some stimuli in the environment, and cue exposure therapy can teach patients with anger-related disorders to reduce their anger behaviours in relation to these triggers. Cue exposure therapy is an established treatment for anxiety disorders (Bahi & Dreyer, 2020 ; Javanbakht, 2018 ; Loucks et al, 2019 ; Nonkes et al, 2012 ; Stenmark et al, 2013 ). Other studies have also shown that cue exposure therapy can effectively decrease anger feelings (Stapleton et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This mouse finding is in accordance with other recent rodent data, showing that pronounced effects of ethanol characterise animals expressing maladaptive behavioural responses to stress. These effects were observed either with the CPP paradigm (Bahi & Dreyer, 2014; Bahi & Dreyer, 2020; Macedo et al, 2018; Yu et al, 2016), with the two‐bottle free choice paradigm (Cannady et al, 2021; Manjoch et al, 2016; Meyer et al, 2013) or with the self‐administration paradigm (Barchiesi et al, 2021; Edwards et al, 2013; Makhijani et al, 2021). Nevertheless, studies with other drugs (such as cocaine and methamphetamine) have shown that stress does not necessarily lead to potentiate the effect of the drug or increase its consumption (e.g., cocaine: Enman et al, 2015; Hadad et al, 2016; Lguensat et al, 2021; methamphetamine: Eagle & Perrine, 2013).…”
Section: Discussionmentioning
confidence: 99%
“… Bahi (2017) observed that the increased anxiety-like behavior, the increase in ethanol intake and the appearance of ethanol-induced CPP were buffered by exposure to EE conditions after the stress experience. In a more recent study, EE also proved to counteract social stress effects favoring the extinction of memories associated with ethanol and reducing reinstatement of drug seeking ( Bahi and Dreyer, 2020 ).…”
Section: Discussionmentioning
confidence: 99%